الإمام الحافظ أبو نعيم الفضل بن دكين ومنهجه في الجرح والتعديل - مهدي، أيمن (جامعة الملك عبدالعزيز, 2021)
تناول هذا البحث دراسة حياة الإمام أبي نعيم الفضل بن دكين، وبيان مكانته وأثره في علم الحديث عمومًا، وفي الجرح والتعديل خصوصًا، والكشف عن منهجه في الحكم على الرجال، من خلال جمع أقواله المنتشرة في كتب الجرح والتعديل، ومقارنتها بأقوال غيره من النقاد، بغرض الوقوف على مدى موافقتهم أو مخالفتهم له، ثم التوصل إلى خصائص منهجه في نقد الرجال.
this research deals with studying the life of Imam Abu Na'im al-Fadl bin Dukain, stating his position and impact on hadith science in general, and in wounding and modification in particular, and revealing his approach to judging men, by collecting his words spread in the books of wound and modification, and comparing them with the sayings of other critics, with the aim of Determining the extent of their approval or disagreement with him, then arriving at the characteristics of his approach to criticizing men.
Keywords: الأحاديث النبوية -- رواة الحديث -- النقد الحديثي -- علم الجرح والتعديل -- أعلام المحدثين -- الفضل بن دكين، عمرو بن حماد بن زهير، ت. 219 هـ